Becoming frum : how newcomers learn the language and culture of Orthodox Judaism - Benor, Sarah, 1975- (New Brunswick, NJ : Rutgers University Press, 2012)
When non-Orthodox Jews become frum (religious), they encounter much more than dietary laws and Sabbath prohibitions. They find themselves in the midst of a whole new culture, involving matchmakers, homemade gefilte fish, and Yiddish-influenced grammar. Becoming Frum explains how these newcomers learn Orthodox language and culture through their interactions with community veterans and other newcomers.
Introduction : Orthodox Jews and language socialization -- "Now you look like a lady" : adventures in ethnographic and sociolinguistic fieldwork -- "He has tzitzis hanging out of his ponytail" : Orthodox cultural practices and how bts adapt them -- "This is not what to record" : Yiddish, Hebrew, and the English of orthodox Jews -- "Torah or toyrah" : language and the modern orthodox to black hat continuum -- "Just keepin' it real, mamish" : why ba'alei teshuva adopt (or avoid) Orthodox language -- "I finally got the lingo" : progression in newcomers' acquisition of Orthodox language -- "A ba'al teshuva freak" : distinguishing practices of newly Orthodox Jews -- Matisyahu and my fair lady : reflections on adult language socialization.
Includes bibliographical references and index.
Master record variable field(s) change: 072, 082 - OCLC control number change
Keywords: Jewish way of life; Jews -- Return to Orthodox Judaism; Orthodox Judaism -- Social aspects; Hebrew language -- Social aspects; Yiddish language -- Social aspects; Sociolinguistics; RELIGION -- Judaism -- Orthodox; Hebrew language -- Social aspects; Jewish way of life; Jews -- Return to Orthodox Judaism; Orthodox Judaism -- Social aspects; Sociolinguistics; Yiddish language -- Social aspects; Electronic books